2022
DOI: 10.1071/cp22002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression profile analysis of the

Abstract: Context Soybean cyst nematode is the most important pest of soybean (Glycine max (L.) Merr.) worldwide, causing serious yield losses. Lignin is a vital component of the cell wall that can provide resistance to cyst nematode. O-Methyltransferase (OMT) is a key enzyme involved in lignin metabolism in the phenylalanine pathway. Aims In this study, the soybean OMT gene family was systematically identified, and the expression response of GmOMT to abiotic and cyst nematode stresses was investigated. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…To better understand the role of CmOMTs in the response to abiotic and biotic stresses, we analyzed the type, number, and distribution of cis -acting elements of 21 CmOMTs in the promoter. Light-responsive elements were present in all CmOMTs , suggesting that the expression of CmOMTs may be regulated by light, similar to previous studies on soybeans ( Zhao et al, 2022 ). In addition, the number of hormone-response cis -acting elements and stress-response cis -acting elements suggests that CmOMT family members may be extensively involved in growth, development, and environmental stress.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To better understand the role of CmOMTs in the response to abiotic and biotic stresses, we analyzed the type, number, and distribution of cis -acting elements of 21 CmOMTs in the promoter. Light-responsive elements were present in all CmOMTs , suggesting that the expression of CmOMTs may be regulated by light, similar to previous studies on soybeans ( Zhao et al, 2022 ). In addition, the number of hormone-response cis -acting elements and stress-response cis -acting elements suggests that CmOMT family members may be extensively involved in growth, development, and environmental stress.…”
Section: Discussionsupporting
confidence: 88%
“…Analyses of plant evolutionary relationships have shown that genes with similar intron-exon structures and conserved motif arrangements often have similar functions ( Long, Souza & Gilbert, 1995 ). Most members of the same taxon of the 67 OMTs in soybean have similar gene structures, and the same results have been observed in pomegranate and rice ( Zhang et al, 2021a ; Zhang et al, 2021b ; Zhao et al, 2022 ; Liang et al, 2022 ). In our study, 21 CmOMTs were classified as class I, class II, and class III, which consisted of nine, six, and six members, respectively.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…COMT from soybean, tomato, apple, and grape were separated into clades D and E with distant related indicating the evolutionary constancy of COMTs between species and their functional differentiation. Differential expression patterns of COMT in different tissues of soybean and grape also suggested their functional diversity in response to abiotic stress 98,99 . Similarly, COMT in apple to a common ancestor has undergone duplication, generating two clusters with different functions 100 .…”
Section: Melatonin Biosynthesismentioning
confidence: 99%
“…Differential expression patterns of COMT in different tissues of soybean and grape also suggested their functional diversity in response to abiotic stress. 98,99 Similarly, COMT in apple to a common ancestor has undergone duplication, generating two clusters with different functions. 100 In addition, tandem or segmental duplication of COMT in Arabidopsis implied their conservative functions in coping with abiotic stress.…”
Section: Abiotic Stressmentioning
confidence: 99%